Toxin profile of Ostreopsis cf. ovata from Portuguese continental coast and Selvagens Islands (Madeira, Portugal). (15th July 2020) - Soliño, Lucía; García-Altares, María; Godinho, Lia; Costa, Pedro Reis
Abstract: The toxigenic dinoflagellate Ostreopsis cf. ovata is known to produce a range of palytoxin (PLTX) - related compounds named ovatoxins (OVTX). O. cf. ovata presents a wide variability in toxin production and its toxic profile is strain-specific. Several OVTXs, denominated from -a to -h and -l have been reported from different strains of this benthic microalgae up to now, mainly in Mediterranean isolates. However, less is known about the toxin profile of the strains present in the Atlantic coasts of Europe. In this work, strains of O. cf. ovata isolated from the South coast of Portugal mainland (Algarve) and Selvagens Island (Madeira, Portugal) were cultured and tested for toxicity by hemolytic assay. Toxin profiles were qualitatively elucidated by Liquid Chromatography-High Resolution Mass Spectrometry (LC-HRMS). The strain from Algarve presented lower toxic potency than the strain from Selvagens island (12.3 against 54.8 pg of PLTX equivalents per cell) showing in both cases the characteristic toxin profile of Mediterranean strains. The major component, OVTX-a, was concomitant with OVTX from -b to -g and isobaric PLTX. Regarding the morphological characteristics of these strains, as well as their toxin fingerprint, it is likely they are closely related to strains from Mediterranean coasts. The present study reports for the first time the occurrence of several OVTX congeners and iso-PLTX in O. cf. ovata from Portuguese waters. This study provides valuable information to characterize the risk of OVTXs-related outbreaks in Portugal. Highlights: Toxin profile of two strains of Ostreopsis cf. ovata from Portugal is reported. Both strains present similar toxin profile but differ in toxic potency. Blooms of O. cf. ovata in Algarve and Madeira may pose a risk for public health.